2009
DOI: 10.1074/jbc.m109.015727
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Studies Reveal the Functional Role of Bicovalent Flavinylation in Berberine Bridge Enzyme

Abstract: Berberine bridge enzyme (BBE) is a member of the recently discovered family of bicovalently flavinylated proteins. In this group of enzymes, the FAD cofactor is linked via its 8␣-methyl group and the C-6 atom to conserved histidine and cysteine residues, His-104 and Cys-166 for BBE, respectively. 6-S-Cysteinylation has recently been shown to have a significant influence on the redox potential of the flavin cofactor; however, 8␣-histidylation evaded a closer characterization due to extremely low expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 33 publications
0
46
0
2
Order By: Relevance
“…34,35,308315 The enzyme converts ( S )-reticuline ( 118 ) derived from L-tyrosine, to ( S )-scoulerine ( 443 ) which is on the way to more complex benzophenanthridine alkaloids including berberine ( 205 ). BBE constructs a new C-C bond between the N- methyl and the catechol ring in 443 as shown in Scheme 61.…”
Section: Nonradical Cyclization Mechanismsmentioning
confidence: 99%
“…34,35,308315 The enzyme converts ( S )-reticuline ( 118 ) derived from L-tyrosine, to ( S )-scoulerine ( 443 ) which is on the way to more complex benzophenanthridine alkaloids including berberine ( 205 ). BBE constructs a new C-C bond between the N- methyl and the catechol ring in 443 as shown in Scheme 61.…”
Section: Nonradical Cyclization Mechanismsmentioning
confidence: 99%
“…[11,12] Only recently, BBE from Eschscholzia californica (California poppy) could be expressed efficiently in Pichia pastoris [13] to give a sufficient quantity of the enzyme for crystallization and investigation of the mechanism. [10,14] Thus, BBE has been thoroughly investigated regarding its biochemical properties and catalytic mechanism, while its potential as a biocatalyst for preparative transformation of non-natural substrates has not been explored yet. A major concern referred to the question whether non-natural substrates could be transformed at all, since plant enzymes may have strict substrate specificity.…”
mentioning
confidence: 99%
“…The enzyme contains a bicovalently bonded flavin responsible for the reaction. [21] Recently, it could be shown that recombinant BBE from Eschscholzia californica (California poppy) [22,23] can be employed efficiently for the preparation of novel optically pure isoquinoline and berbine alkaloids via enantioselective oxidative C À C bond formation.[24] The enzyme displayed perfect enantioselectiviScheme 1. Natural reaction catalysed by the berberine bridge enzyme (BBE).…”
mentioning
confidence: 99%